واقع التكفل النفسي بالطفل التريزومي 21 تقرير ميداني بالمركز النفسي البيداغوجي للأطفال المعوقين ذهنيا بالوادي - ضيف, الأزهر; الأشراف, فطيمة الزهرة (My University, 2018)
يعتبر ذوو الاحتياجات الخاصة طاقة بناءة يمكن الاستفادة منها في تنمية المجتمع خاصة إذا ما تم إرشادهم بطريقة تساعدهم على معرفة طبيعة البيئة التي يعيشون فيها ويؤدون أدوارهم من خلالها حيث يتعلمون أهم الأساليب الفعالة للقيام بشؤونهم اليومية ومواجهة مشكلاتهم لأنهم يختلفون عن الأشخاص العاديين من حيث أنهم لا يستطيعون التكيف بسهولة نتيجة لنمو مشاعر النقص والرفض لديهم وذلك بسبب إعاقتهم. إلا أنه لا يتأتى لأي مجتمع من المجتمعات استغلال هذه الطاقات إلا من خلال الاهتمام بهذه الشريحة وتوفير سبل التكفل بها ورعايتها على الوجه الأمثل، ومن بين المؤسسات التي توكل لها هذه المهام نذكر المراكز النفسية البيداغوجية سواء الخاصة منها بالتكفل بالمعاقين ذهنيا أو المعاقين سمعيا أو المكفوفين. وعليه نحاول التطرق في هذا الطرح إلى واقع التكفل النفسي بالطفل التريزومي 21 المنتسب لمثل هذه المراكز في الجزائر. the actuality of undertaking Mongolian children 21: fieldreport in the psychological centre of the mental hampered children in El Oued. Abstract: People with special needs are considered as constructine energy that can be utilized in community development especially if they are guided in a way that helps them to know the nature of the environment in wich they live and perform their roles through them where they learn the most effective methods to carry out their daily affairs and face their problems because they differ from ordinary people in that they cannot adapt easily due to the growth of feelings deprivation and rejection because of their disability. but it is not possible for any community and any of its institutions to exploit these energies only through interest in this segment and the provision of ways to ensure and care for the same face. At the forefront of these tasks is the psychological centers of children with mental disabilities. Therefore, we try to address in this presentation the reality of the undertaking of the Mongolian children 21 belonging to such centers in Algeria
the actuality of undertaking Mongolian children 21: fieldreport in the psychological centre of the mental hampered children in El Oued.
مجلة الدراسات والبحوث الاجتماعية المجلد 06 العدد 02 جامعة الوادي
Keywords: التكفل النفسي، الطفل، التريزومي 21.; the undertaking, the child, Mongolian children 21